An assessment of housing affordability index at districts level in Kelantan - Mohamed Osman, Mariana; Zainudin, Farah Eleena; Rabe, Noor Suzilawati; Hitam, Mizan; Abdullah, Muhammad Faris (Malaysian Institute Of Planners, 2020)
The purpose of this paper is to assess the housing affordability level in every district in Kelantan. The goal of this study is to determine the affordability level and the affordable housing price in every district in Kelantan. In order to determine the housing affordability level, the Price-to-Income Ratio approach or known as median multiple is used in this study. The study found that the overall affordable leve in Kelantan from 2012, 2014 to 2016 has increased from 4.5 to 4.8 to 5.4 which clearly showed the level worsen over the years. In term of afforadablee housing price, the Kelantan median house price for 2016 was RM199,900 but using median multiple calculation using the income data, the maximum affordable house price should be within RM 110,844, which clearly showed that the current housing prices is severely unafforable for Kelantan State.